Perlindungan Hukum Bagi Konsumen Dalam Pengembalian Uang Yang Berbentuk Donasi Pada Minimarket - Anak Agung Ayu Desy Nadhira Putri; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2024)
The practice of diverting customers' change to donations in minimarkets is an important issue in the context of consumer protection. The concept of the rule of law suggests that diverting consumers' money to donations violates legal principles. This research identifies two main problems: 1) Consumer protection arrangements related to donation refunds in minimarkets; 2) Forms of legal protection for consumers whose change is diverted into donations at minimarkets. The research method uses a normative legal approach with a focus on legislation and concepts. The results show that this practice violates the Consumer Protection Law, and is not in accordance with the Currency Law and Bank Indonesia Law. Consumers are entitled to a refund in the form of rupiah, in accordance with payments that exceed the selling value of goods or services. If consumers suffer losses, the Consumer Protection Law provides protection both preventively and repressively.